Willingness to pay for second generation bioethanol: a contingent valuation approach - Alvarado Nuñez, Vanessa Fiorella (2024)
Increasing the use of biofuels to reduce pollution is an effort in many countries. An alternative that is starting to be marketed internationally, which reduces greenhouse gas emissions and applies circular economy for its production is second-generation bioethanol (E2G); however, in Peru there are no policies for its commercialization in the current gasohol blend. This study will determine consumer's willingness to pay (WTP) for E2G by applying surveys using the double-bounded dichotomous choice contingent valuation method (CVM). A total of 472 consumers of premium and regular gasohol in Metropolitan Lima were asked about their WTP for E2G, demographic characteristics, vehicle usage and level of perception related to the environment. It was found that users of premium and regular gasohol would be willing to pay a premium of 10.40% and 7.03% respectively. Likewise, it was obtained that people who have a higher perceived consumer effectiveness (PCE) are more likely to pay a premium for E2G.